Pengaruh Kepemimpinan, Komitmen Afektif Dan Keterlibatan Kerja Terhadap Kepuasan Kerja Pada Guru Sd Se-Kecamatan Wanasalam - Syahrosi Syahrosi; M. Iqbal; Ahmad Sugianto; Hadi Subhan (E-Journal Studia Manajemen, 2022)
This study aims to obtain information regarding the possibility of whether job satisfaction is influenced by leadership, effective commitment and involvement. Using a causal study through a survey of elementary school teachers throughout Wanasalam District, for a population of 110 using the Cooper method, which is taking a percentage, the sample is 33 teachers. The sampling technique used is random sampling of the sample. The method used in this study is a quantitative survey method, while the analytical techniques used are correlation and regression. The results prove that there is an influence between leadership on job satisfaction. there is an effect between effective commitment to job satisfaction. there is an influence between job involvement on job satisfaction. there is an effect of leadership, effective commitment and work involvement together on job satisfaction. These findings indicate that organizations need to consider the variables of leadership, affective commitment, and work involvement in planning and human resource development in SD throughout Wanasalam District.